2010
DOI: 10.1021/ja908282f
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Formaldehyde-Induced Cross-Links Between Amino Acids and Deoxynucleosides and Their Oligomers

Abstract: Exposure to formaldehyde results in the formation of DNA-protein cross-links (DPCs) as a primary genotoxic effect. Although DPCs are biologically important and eight amino acids have been reported to form stable adducts with formaldehyde, the structures of these cross-links have not yet been elucidated. We have characterized formaldehyde-induced cross-links of Lys, Cys, His and Trp with dG, dA and dC. dT formed no cross-links, nor did Arg, Gln, Tyr or Asn. Reaction of formaldehyde with Lys and dG gave the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
134
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(146 citation statements)
references
References 27 publications
(60 reference statements)
6
134
0
Order By: Relevance
“…In comparing the products of reactions containing lysine, cysteine, histidine, or tryptophan with each of the four DNA bases, the highest yield of crosslinked product was obtained with lysine and deoxyguanosine (51), consistent with lysine being the most reactive among residues in native proteins as described above. Similar results were obtained using short peptides and trinucleotides (51). In the context of protein-DNA interactions, the first chemical step could involve reaction with an amino acid side chain in a protein, the protein N terminus, or an amino or imino group on a DNA base; importantly, however, the ⑀-amino group on the lysine side chain is a better nucleophile than are the amino/imino groups on DNA bases whose lone pair electrons are delocalized in the aromatic ring.…”
Section: Capture Of Protein-dna Complexessupporting
confidence: 85%
“…In comparing the products of reactions containing lysine, cysteine, histidine, or tryptophan with each of the four DNA bases, the highest yield of crosslinked product was obtained with lysine and deoxyguanosine (51), consistent with lysine being the most reactive among residues in native proteins as described above. Similar results were obtained using short peptides and trinucleotides (51). In the context of protein-DNA interactions, the first chemical step could involve reaction with an amino acid side chain in a protein, the protein N terminus, or an amino or imino group on a DNA base; importantly, however, the ⑀-amino group on the lysine side chain is a better nucleophile than are the amino/imino groups on DNA bases whose lone pair electrons are delocalized in the aromatic ring.…”
Section: Capture Of Protein-dna Complexessupporting
confidence: 85%
“…Characterization and In Vitro Degradation of Formaldehyde-Induced DPCs Based on previous work in our lab (Lu et al, , 2010b, dG-Me-GSH and dG-Me-AGT are formed in vitro and contain specific dG-Me-Cysteine linkages (Fig. 1A).…”
Section: Resultsmentioning
confidence: 88%
“…Previous in vitro studies demonstrated DPCs were induced by formaldehyde with formation of N-CH 2 -N and N-CH 2 -S linkages between DNA and protein (Heck et al, 1990). To study the chemical identity of formaldehyde-induced DPCs, we investigated the in vitro crosslinking reaction between nucleosides, nucleotides, and amino acids and peptides in the presence of formaldehyde (Lu et al, 2010b). Our results demonstrate that the most abundant crosslink was formed with N-CH 2 -N linkage between dG and lysine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations